IMPROVING IPS LEARNING RESULTS THROUGH THE APPLICATION OF CLASS IV THINK PAIR SHARE COOPERATIVE LEARNING MODELS IN SD NEGERI 6, SUKAJADI, PEKANBARU CITY - Paridamiwati (JURNAL RANDAI, 2021)
The phenomenon of low student learning outcomes from observations of researchers in the field is caused by several factors, such as: (1) The learning carried out by the teacher still uses conventional learning, namely the teacher lectures in delivering material, questions and answers and assignments, so it does not provide encouragement for students to study seriously ; (2) In delivering learning, the teacher still places students as recipients so that students are passive and only wait for information from the teacher without trying to find it. This can be seen when the teacher asks for students' opinions, only a few students give opinions and ask questions about things that are not understood; (3) This is also due to the lack of teacher knowledge about learning strategies that can activate students; (4) Teachers do not provide opportunities for students to work together in doing their assignments with their friends. This makes researchers feel the need to improve the learning process with efforts made to apply an appropriate learning model, namely the Think Pair Share Type cooperative learning model. This type gives students time to think and respond and help each other. Cooperative learning Think Pair Share is a cooperative learning model that allows students to help each other and cooperate with one another. Through this model students are more enthusiastic in learning so that they can increase the achievement of optimal learning outcomes. The formulation of the problem is as follows: "Does the student learning outcomes increase through the application of the Think Pair Share type of cooperative learning model for fourth grade students of SD Negeri 6 Sukajadi, Pekanbaru City?". The purpose of this study was to determine the improvement of social studies learning outcomes through the application of the Think Pair Share Type Cooperative learning model for class IV SDN 6 Sukajadi, Pekanbaru City. Based on the data that has been presented above, it is concluded that the application of the Think Pair Share (TPS) cooperative learning model can improve social studies learning outcomes for fourth grade students of SD Negeri 6 Sukajadi (the average student learning outcomes through cycle I is 62.25, while in the second cycle the average student learning outcomes of 76.25)